The Civil Description for Bio Property in World Heritage List - Alabid, Sadkhan Madhloom Bahedh; Mizher, Haider Ali (Journal of Ecohumanism, 2024)
The civil description of the biological component means the center of the financial component to the value of the biological component within the marshes.There are two aspects in the statement of the civil description. The first aspect is the description of the subject of the biological component in that it is property in the technical sense of ownership and thus it is formed. Financial transactions are linked to it from the perspective of financial exchange value and the usual civil relations are conducted over it.Or it departs from the transaction in the traditional sense by giving priority to the legal value of the moral inheritance, and thus the transaction is linked to this legal description.Here, the addition of the marshes to the World Heritage List establishes a dialectic within the scope of the internal status of civil descriptions being distinct from the nature of UNESCO’s relations and regulations in the nature of the moral heritage of the marshes, including the biological component.